2018
DOI: 10.3390/molecules23071823
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Chemical Fingerprint Analysis for the Quality Evaluation of Platycodi Radix Collected from Various Regions in China by HPLC Coupled with Chemometrics

Abstract: Platycodi Radix (PR) is the root of Platycodon grandiflorum (Jacq.) A. DC., which has been used for a long time in China to treat pulmonary diseases. The present study aimed to evaluate the quality of PR samples collected from 23 regions of 11 provinces in China. Eight saponins were quantified using HPLC coupled with evaporative light scattering detection (HPLC-ELSD). The samples with the highest total contents of saponins were from southern China, such as Yunnan, Guangxi, Jiangxi, and Guangzhou. The fingerpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…All evaluation tests confirmed that there was little or no herbal extract-excipient interaction indicative that the granules formed were stable [39,40,41]. The formulation technology employed is beneficial for industrial applications, in the potential ease of scaling up, ease of formulation, enhanced stability of therapeutic principles and reproducibility coupled with the use of unsophisticated equipment, A simple, convenient, cost effective, and environmentally friendly method is a beneficial approach.…”
Section: Discussionmentioning
confidence: 85%
“…All evaluation tests confirmed that there was little or no herbal extract-excipient interaction indicative that the granules formed were stable [39,40,41]. The formulation technology employed is beneficial for industrial applications, in the potential ease of scaling up, ease of formulation, enhanced stability of therapeutic principles and reproducibility coupled with the use of unsophisticated equipment, A simple, convenient, cost effective, and environmentally friendly method is a beneficial approach.…”
Section: Discussionmentioning
confidence: 85%
“…For these reasons, individual brands of herbal medicines from the same plant species may differ significantly in their biological activity and chemical composition. Therefore, quality control for chemical consistency is essential to ensure the efficacy of herbal medicines (Viapiana et al 2016;Lu et al 2018). Health organizations, including the US Food and Drug Administration (FDA), the World Health Organization (WHO), and the European Medicines Agency (EMA), have recommended this strategy for the evaluation of quality and similarity in herbal medicines (Xie et al 2019;Zhu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A HPLC-PAD method was developed for the quality evaluation of ASR. In consideration of the complexity of TCM, similarity analysis (SA), hierarchical clustering analysis (HCA) and principal component analysis (PCA) which were usually performed in analysis, 37 , 44 , 75 - 78 were used to reasonably define the class of ASR and to efficiently evaluate the quality of ASR. We expected that the method would be helpful for the quality control of ASR and it can provide a reference for the quality evaluation of products prepared by traditional decoction technology, such as classical preparations.…”
Section: Introductionmentioning
confidence: 99%